An affinity for justice: ethics and apologetics in Lactantius' response to persecution - MacKerras, KH (2021)
This thesis discusses Lactantius’ moral philosophy and understanding of justice, and explores the apologetic use he made of these ideas. The present study is the fullest treatment of Lactantius’ view of justice in any language, and the only one in English. Its methodology is philological; it combines a close reading of Lactantius’ corpus with a literary-historical investigation of the many sources he cites and of the ideological justification of the Diocletian persecution. I investigate how these sources govern the form and content of Lactantius’ arguments; his apologetic method means he often argues for Christian ideas from pagan sources and premises. Lactantius understands justice as meeting obligations and divides obligations into two domains: duties to God and duties to other humans. He does so by likening God to a Roman paterfamilias, which creates the obligations of worshipping God and of treating other humans as his children and one’s siblings. Lactantius arrives at this definition by reconfiguring Cicero’s understanding of natural law, which undergirds justice in de Legibus Book 1. Lactantius’ conception of justice thus adopts a Ciceronian framework, but fills it with Christian ideas which drive his ethics. Lactantius’ ethics were influenced by Cyprian’s selection of biblical quotations in ad Quirinum; contra Wlosok and Loi, I found no profound dependence upon the Hermetica. The study then situates Lactantius’ ethics in the intellectual context of his day. Lactantius’ understanding of justice is carefully constructed to respond holistically to the persecutors’ ideology and asserts that Christians embody the ideals of Roman virtue. Contrary to the suggestions of Digeser and Colot, he does not seek to Christianise the Roman empire, but rather to dissuade it from persecuting Christians.